0
$\begingroup$

Could someone help find identities for these two?

I started with

$ζ^\star(2,1,2)$ = $\sum_{k=1}^{\infty}(\frac{1}{k^2})\sum_{l=1}^{k}(\frac{1}{l})\sum_{m=1}^{l}(\frac{1}{m^2})$

and

$ζ^\star(\bar{2},\bar{1},2)$ = $\sum_{k=1}^{\infty}(\frac{((-1)^k}{k^2})\sum_{l=1}^{k}(\frac{(-1)^l}{l})\sum_{m=1}^{l}(\frac{1}{m^2})$

but I've only worked on zeta functions with depth 2, so I'm not really sure how to proceed.

Thanks!

$\endgroup$
  • $\begingroup$ The first is $+\infty$ or undefined, depending on how you take it. $\endgroup$ – Thomas Andrews Sep 9 at 2:42
  • $\begingroup$ See arxiv.org/pdf/math/9910045.pdf $\endgroup$ – reuns Sep 9 at 3:43
  • $\begingroup$ @ThomasAndrews did you perhaps misread the summations? The innermost sum has order $\theta(\ell^{-1})$, so the terms on the second sum are $\theta(\ell^{-2})$, and its sum is thus of order $\theta(k^{-1})$, which means that the terms in the outermost sum are $\theta(k^{-3})$ and it's decidedly convergent... $\endgroup$ – Steven Stadnicki Sep 9 at 17:13
  • $\begingroup$ @StevenStadnicki It is because at first the OP wrote $\sum_{l=1}^\infty$ $\endgroup$ – reuns Sep 9 at 20:57
  • $\begingroup$ @reuns D'oh, I should've checked the edit history first. Thank you, and my apologies! $\endgroup$ – Steven Stadnicki Sep 9 at 21:47
1
$\begingroup$

With a bit of patience, summation by parts reduces

$$ \zeta^\star(2,1,2) = \sum_{k\geq 1}\frac{1}{k^2}\sum_{l=1}^{k}\frac{H_l^{(2)}}{l} $$ to $\sum_{k\geq 1}\frac{H_k H_k^{(2)}}{k^2}$, which is computable through the Maclaurin series of $\arcsin^4(x)$, and $$ \sum_{k\geq 1}\frac{1}{k^2}\sum_{l=1}^{k}\frac{H_l}{l^2}= 2\zeta(2)\zeta(3)-\sum_{k\geq 1}\frac{H_{k+1}H_k^{(2)}}{(k+1)^2}, $$ so the determination of $ \zeta^\star(2,1,2)$ can be considered as already solved by nospoon.

$\endgroup$

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.